Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To rewrite the given quadratic equation [tex]\( x^2 + 4x + 1 = 10 \)[/tex] by completing the square, follow these steps:
1. Move the constant term to the other side:
[tex]\[ x^2 + 4x + 1 - 10 = 0 \][/tex]
Simplify it to:
[tex]\[ x^2 + 4x - 9 = 0 \][/tex]
2. Shift the constant term on the left side to the right:
[tex]\[ x^2 + 4x = 9 \][/tex]
3. To complete the square, find the constant needed to form a perfect square trinomial.
Start by taking half of the coefficient of [tex]\( x \)[/tex] (which is 4), then squaring it:
[tex]\[ \left(\frac{4}{2}\right)^2 = 4 \][/tex]
4. Add and subtract this constant (4) inside the equation:
[tex]\[ x^2 + 4x + 4 - 4 = 9 \][/tex]
Combine the terms to get:
[tex]\[ x^2 + 4x + 4 = 9 + 4 \][/tex]
5. Rewrite the left-hand side as a square:
[tex]\[ (x + 2)^2 = 13 \][/tex]
Thus, the equivalent form of the quadratic equation [tex]\( x^2 + 4x + 1 = 10 \)[/tex] after completing the square is:
[tex]\[ (x + 2)^2 = 13 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{B. (x + 2)^2 = 13} \][/tex]
1. Move the constant term to the other side:
[tex]\[ x^2 + 4x + 1 - 10 = 0 \][/tex]
Simplify it to:
[tex]\[ x^2 + 4x - 9 = 0 \][/tex]
2. Shift the constant term on the left side to the right:
[tex]\[ x^2 + 4x = 9 \][/tex]
3. To complete the square, find the constant needed to form a perfect square trinomial.
Start by taking half of the coefficient of [tex]\( x \)[/tex] (which is 4), then squaring it:
[tex]\[ \left(\frac{4}{2}\right)^2 = 4 \][/tex]
4. Add and subtract this constant (4) inside the equation:
[tex]\[ x^2 + 4x + 4 - 4 = 9 \][/tex]
Combine the terms to get:
[tex]\[ x^2 + 4x + 4 = 9 + 4 \][/tex]
5. Rewrite the left-hand side as a square:
[tex]\[ (x + 2)^2 = 13 \][/tex]
Thus, the equivalent form of the quadratic equation [tex]\( x^2 + 4x + 1 = 10 \)[/tex] after completing the square is:
[tex]\[ (x + 2)^2 = 13 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{B. (x + 2)^2 = 13} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.